2014
DOI: 10.1002/2013jc009284
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of sporadic physical processes driving temperature and nutrient high‐frequency variability in the coastal ocean off southeast Australia

Abstract: [1] Physical processes forced by alongshore winds and currents are known to strongly influence the biogeochemistry of coastal waters. Combining in situ observations (moored platforms, hydrographic surveys) and satellite data (sea surface wind and sea surface height), we investigate the transient occurrence of wind-driven upwelling/downwelling and current-driven upwelling events off southeast Australia. Remote-sensed indices are developed and calibrated with multiannual time series of in situ temperature and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 45 publications
(125 reference statements)
5
52
0
Order By: Relevance
“…Gräwe et al (2010) found evidence of a sporadic upwelling event just to the north of Sandy Cape at 24.5 o S in hydrography data from a Hervey Bay survey during December 2007. Rossi et al (2014) focused their analysis of eastern coastal upwelling on a region south of 28 o S using 10 years of remotely sensed wind data. It was found that upwelling favourable winds may occur 3-6 days per month on average during the August to December period, at the same time when current-driven upwelling is at a maximum, and less than 2 days per month during other months that appear to be dominated by wind-driven downwelling conditions.…”
Section: Description Of the Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Gräwe et al (2010) found evidence of a sporadic upwelling event just to the north of Sandy Cape at 24.5 o S in hydrography data from a Hervey Bay survey during December 2007. Rossi et al (2014) focused their analysis of eastern coastal upwelling on a region south of 28 o S using 10 years of remotely sensed wind data. It was found that upwelling favourable winds may occur 3-6 days per month on average during the August to December period, at the same time when current-driven upwelling is at a maximum, and less than 2 days per month during other months that appear to be dominated by wind-driven downwelling conditions.…”
Section: Description Of the Study Sitementioning
confidence: 99%
“…Along the EAC-influenced eastern coast of Australia, studies by Andrews and Gentien (1982), Griffin et al (1987), Hallegraef and Jeffrey (1993), Middleton et al (1994), Oke andMiddleton (2000, 2001), Middleton (2002, 2004), Weeks et al (2010), Thompson et al (2011), Wood et al (2012), Schaeffer et al (2013), Everett et al (2014), Armbrecht et al (2014), and Rossi et al (2014) provided significant insight into the location, frequency and the physical mechanisms of Australian east coast upwelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more productive regions of Australia's Exclusive Economic Zone (EEZ) include the northern continental shelves along the Gulf of Carpentaria and around to the Kimberley (Condie and Dunn 2006;Furnas and Carpenter 2016). The Leeuwin Current and the EAC have generally lower levels of productivity (Hanson et al 2005;Thompson et al 2011a;Everett and Doblin 2015), despite the existence of hot spots (Rossi et al 2014;Brieva et al 2015). The more productive regions of Australia's EEZ include the northern continental shelves along the Gulf of Carpentaria and around to the Kimberley (Rothlisberg et al 1994).…”
Section: Oceanographymentioning
confidence: 99%
“…Likewise, intermittent high productivity events caused by physical forcing are known to occur in the region (e.g. McKinnon et al 2011;Rossi et al 2013aRossi et al , 2014. The Sahul Shoals, located to the east of the CSB stations at water depths of 30-40 m, are also a potential source of highly labile OM to the CSB sediments that is derived from benthic production.…”
Section: Om Reactivitymentioning
confidence: 99%